2008
DOI: 10.1080/09553000701691679
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 7, 14 and 21 Hz modulated 450 MHz microwave radiation on human electroencephalographic rhythms

Abstract: Our findings suggest that the effect of the 450 MHz microwave radiation modulated at 7, 14 and 21 Hz varies depending on the modulation frequency. The microwave exposure modulated at 14 and 21 Hz enhanced the EEG power in the alpha and beta frequency bands, whereas no enhancement occurred during exposure to the modulation frequency of 7 Hz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 24 publications
3
65
0
2
Order By: Relevance
“…This suggests that different modulation techniques (e.g., temporal power variation, modulation frequency) in different mobile phone systems may be a biologically relevant factor [Pedersen and Andersen, 1999;Bachmann et al, 2005;Hinrikus et al, 2007Hinrikus et al, , 2008. In addition, the majority of null findings in the literature may be due to the low power level of mobile phone radiation because most studies were designed to give local SAR values at or near the permitted limits.…”
Section: Discussionmentioning
confidence: 89%
“…This suggests that different modulation techniques (e.g., temporal power variation, modulation frequency) in different mobile phone systems may be a biologically relevant factor [Pedersen and Andersen, 1999;Bachmann et al, 2005;Hinrikus et al, 2007Hinrikus et al, , 2008. In addition, the majority of null findings in the literature may be due to the low power level of mobile phone radiation because most studies were designed to give local SAR values at or near the permitted limits.…”
Section: Discussionmentioning
confidence: 89%
“…An increase in the alpha band activity was observed with the GSM signal, while no effects were seen from the CW signal. Hinrikus et al [2008b] reported that AM of 450 MHz electromagnetic fields at 14 and 21 Hz enhanced EEG power in the alpha and beta frequencies in healthy volunteers, whereas no effect was detected when the modulation frequency was 7 Hz. The same research group investigated the effect of modulation on resting EEG in individual subjects.…”
Section: Nervous System: Human Studiesmentioning
confidence: 95%
“…Indeed, data reported by some authors showed an increase in EEG power in the alpha frequency band (Cook et al 2004;Croft et al 2002Croft et al , 2008Croft et al , 2010Curcio et al 2005;Hinrikus et al 2008;Huber et al 2002;Kramarenko and Tan 2003;Regel et al 2007;Reiser et al 1995), whereas other studies reported a decrease in EEG power or coherence in the alpha band (Maby et al 2006;Perentos et al 2013;Vecchio et al 2007Vecchio et al , 2010Vecchio et al , 2012. Finally, other studies failed to show an effect on EEG power in the alpha bands (D'Costa 2003; Hietanen et al 2000;Röschke and Mann, 1997;Perentos et al 2007).…”
mentioning
confidence: 87%